DEGRADATION OF POLYAMIDE-6 BY MICROBIAL ISOLATES FROM SOLID WASTE DUMPSITES IN LAGOS STATE, NIGERIA (2012)
Polyamide-6 (also known as nylon-6) is one of the biodegradation-resistant synthetic polymers used in the manufacturing of commodity plastic materials. The environmental effects of the persistence of this material in landfill and on surface water bodies pose global problems that endanger public health. Knowledge of the microbial distribution and pattern of their interaction with these plastics will provide the biological resources and scientific basis for the development of sustainable disposal and treatment method. Therefore, microbial degradation of polyamide-6 and its monomers were investigated. Soil samples were randomly collected at five spots to a depth of 15cm and mixed to form composites from each of the three selected dumpsites at Olusosun, Abule-Egba and Isheri-Igando in Lagos state. Microbiological analysis was carried out on the samples on bimonthly intervals over a period of eight months. The fungal and bacterial isolates were screened for their ability to utilize ε-caprolactam (the monomer of the nylon-6) as a sole source of carbon and nitrogen for growth on a synthetic solid medium and were phenotypically characterized. The 16SrRNA gene sequences were used for the molecular typing of the isolates. The isolates with the best growth within 120hrs in ε-caprolactam medium were tested for nylon-6 degradation. Intermediate products in the culture medium were monitored using High Performance Liquid Chromatography (HPLC) while biodegradation of the nylon-6 was monitored using Fourier Transform Infrared Spectroscopy (FTIR), average number molecular mass (Mn) and weight loss. An un-inoculated experiment served as the control. Data obtained were analysed using ANOVA. A total of 64 bacteria and 22 fungi were isolated from the soil samples. Sixteen species of the bacterial isolates made up of the genera Pseudomonas (5), Alcaligenes (3), Corynebacterium (2), Leucobacter (2), Bordetella (1), Proteus (1), Providencia (1) and Lysinibacillus (1) were capable of utilising ε-caprolactam as the sole source of carbon and nitrogen up to a minimum inhibitory concentration of 20 gL-1. The fungi were identified as five species of Aspergillus and a species of Penicillium. Proteus vulgaris utilized 97.2%, Bordetella petrii 92.5%, Pseudomonas aeruginosa (NTS1) 90.5% and Alcaligenes faecalis (2ABA2) 82.3% of 10 gL-1 ε-caprolactam within 120hrs compared to the control experiment. The HPLC analysis of the culture supernatant revealedthe presence of 6-aminohexanoic acid, ε-caprolactam and some un-identified oligomers as the degradation products of the nylon-6 fibre. The changes observed in the FTIR spectra of different functional groups confirmed the effect of microbial degradation of the nylon-6 fibre. Aspergillus niger was the most efficient of the fungi isolates in degrading the polyamide-6. It achieved 29.77 % reduction in polyamide-6 Mn and 23.95 % weight loss. Moreover, P. aeruginosa (NTS1) degraded Polyamide-6 with 12.82 % reduction in Mn and 5.23% weight loss. These changes were found to be significant at p = 0.05. Aspergillus niger and Pseudomonas aeruginosa degraded nylon-6 fibre and this serves as baseline information for the bio-treatment of the nylon polymer.